The XXI century disease and quality of life in older adults in Tarapoto Andrés Bartra - Bartra, Andrés (2013)
Every day is interesting to observe that the aging of the global population is increasing and this has led to interest in learning more about the emotions as wellas the quality of life of older people. The aim of this study was to determine to what extent are related depression and quality of life in older adults Huayco Health Center - Tarapoto. We used a non-experimental, descriptive correlational. Instruments: Beck Depression Inventory (BDI-II) consists of 21 items and Comprehensive Evaluation Form Senior Ministry of Health (Quality of Life section), consisting of 33 items. The psychometric properties of the instruments indicated that are valid and reliable. The results show that there is a highly significant negative relationship between depression and quality of life (r = - 0.432, p <.01). This means that, how much more can be the depression then quality of life will be affected.